Jumat Bersih: Strategi untuk Menguatkan Gotong Royong Siswa Sekolah Dasar melalui Proyek Profil Pelajar Pancasila - Maulina, Fourtina Okta; Indrakurniawan, Machful (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to describe the strengthening of mutual cooperation character education through the "Clean Friday" activity as part of the Pancasila Student Profile Project at Medalem State Elementary School. This research used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The results show that the Clean Friday activity effectively instills the value of mutual cooperation, increases students’ awareness of environmental cleanliness, and strengthens social relationships among students. The main supporting factors include the active involvement of the principal, teachers, and parents. The obstacles faced include a lack of student awareness, limited facilities, and weather conditions. This activity has proven to be a contextual and sustainable medium for character education at the elementary school level.